2008
DOI: 10.1186/1532-429x-10-37
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance of the charcoal heart

Abstract: We report a case of malignant melanoma metastasis to the heart presenting as complete heart block. The highlight of the case is to demonstrate that silent cardiac metastasis is not uncommon and CMR has the potential to characterize these cardiac metastases and should be used routinely as a screening tool for those cancers with a high chance of cardiac involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…118 Visualization of a mass is first performed with simple spin-echo and cine sequences. Tissue characterization can be approached with a number of additional sequences: T1-and T2-weighted spinecho imaging is used to identify melanoma metastasis (high T1 signal because melanin shortens T1) 119 and fibroelastoma (typically located on the aortic valve with high T2 signal) 120 ; fat suppression is used to identify atrial lipomatous hypertrophy and lipoma; first-pass perfusion imaging identifies increased vascularity in benign tumors (hemangioma, myxoma) and in malignant tumors, especially angiosarcoma in the anterior atrioventricular groove; early hypoenhancement at 1 to 2 minutes after injection of gadolinium identifies thrombus 121 ; and late enhancement at 10 minutes after gadolinium shows expanded interstitial space in fibroma. Other important diagnostic features include the shape, location, and containment of the mass, particularly whether tumor extension or invasion of tissue planes has occurred.…”
Section: Other Conditions Cardiac Tumorsmentioning
confidence: 99%
“…118 Visualization of a mass is first performed with simple spin-echo and cine sequences. Tissue characterization can be approached with a number of additional sequences: T1-and T2-weighted spinecho imaging is used to identify melanoma metastasis (high T1 signal because melanin shortens T1) 119 and fibroelastoma (typically located on the aortic valve with high T2 signal) 120 ; fat suppression is used to identify atrial lipomatous hypertrophy and lipoma; first-pass perfusion imaging identifies increased vascularity in benign tumors (hemangioma, myxoma) and in malignant tumors, especially angiosarcoma in the anterior atrioventricular groove; early hypoenhancement at 1 to 2 minutes after injection of gadolinium identifies thrombus 121 ; and late enhancement at 10 minutes after gadolinium shows expanded interstitial space in fibroma. Other important diagnostic features include the shape, location, and containment of the mass, particularly whether tumor extension or invasion of tissue planes has occurred.…”
Section: Other Conditions Cardiac Tumorsmentioning
confidence: 99%
“…From the literature, we acquired a total of 14 articles regarding heart block as a manifestation of cardiac metastasis, as summarized in Table 1 [2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Oral cavity, uterus, and thyroid are the most common primary cancers that metastasize to the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is still also unknown whether CHB would resolve after cancer treatment 2,20 . Our literature review showed that there are only two cases of metastatic CHB that are reversible after undergoing chemotherapy for cardiac metastasis 8,12 , while several other cases showed that CHB is irreversible [2][3][4][5][6][7][9][10][11][13][14][15] . The short life expectancy in patients with metastatic CHB also makes it difficult to follow up on CHB reversibility.…”
Section: Discussionmentioning
confidence: 99%
“…At his autopsy, the heart was extensively involved with black metastases, typical of what is called "charcoal heart." 20 One additional point merits attention. The amount of tumor deposited in the heart of a patient with metastatic melanoma is far greater than that of any other cancer.…”
Section: Special Report Continuedmentioning
confidence: 99%
“…20 Ordinarily, cardiac metastases are clinically silent. When signs or symptoms do arise, pericardial effusion (with or without tamponade) and dysrhythmias are the usual causes.…”
Section: Special Report Continuedmentioning
confidence: 99%